Flap and frame for the treatment of open or infected tibial plateau fracture - Mohd Yusof, Nazri (SICOT: The World Orthopaedic Organisation, 2018)
Introduction: Wound secondary to open fracture or infection in the tibial plateau frequently results in an exposed bone. Gastrocnemius flap in combination with circular frame are ideal method for bone coverage and stabilising the fracture. It allows control of infection and at the same time the knee to be mobilised. Methods: From 2006 till 2018 we treated 11 patients with local flap and circular frame. There were 7 males and 4 females with mean age of 37.4 years old (range 13 to 60). Nine were due to open fractures while 2 due to infection following plating. Six wound were closed with gastrocnemius muscle flap and 5 with gastrocnemius myocutaneous flap. In 3 patients, bone transport was used to reconstruct the bone defect. Results: Nine patients achieved union and control of infection with mean union time of 6 month (range 4 to 15). One patient had bad pin site infection and opted for removal of frame. Conclusions: Local flap with circular frame is an option to treat open or infected tibialplateau fracture. Pin sites infection may be a serious complication which requires frame removal